Burst firing versus synchrony in a gap junction connected olfactory bulb mitral cell network model - O'Connor, Simon; Angelo, Kamilla; Jacob, Tim (Frontiers in Computational Neuroscience, 2012)
A key player in olfactory processing is the olfactory bulb mitral cell (MC). We have used dual whole-cell patch-clamp recordings from the apical dendrite and cell soma of MCs to develop a passive compartmental model based on detailed morphological reconstructions of the same cells. Matching the model to traces recorded in experiments we find: Cm = 1.91 ± 0.20 μF cm-2, Rm = 3547 ± 1934 Ω cm2 and Ri = 173 ± 99 Ω cm. We have constructed a 6 MC gap-junction (GJ) network model of morphologically accurate MCs. These passive parameters were then incorporated into the model with Na+, Kdr and KA conductances and GJs from Migliore et al. (2005). The GJs were placed in the apical dendrite tuft (ADT) and their conductance adjusted to give a coupling ratio between MCs consistent with experimental findings ( 0.04). Firing at 50 Hz was induced in all 6 MCs with continuous current injections (0.05-0.07 nA) at 20 locations to the ADT of two of the MCs. It was found that MCs in the network synchronised better when they shared identical passive parameters rather than using their own passive parameters for the fit suggesting that the OB may have populations of MCs tuned for synchrony. The addition of calcium-activated potassium channels (iKCa) and L-type calcium channels (iCa(L)) (Bhalla and Bower, 1993) to the model enabled MCs to generate burst firing. However, the gap-junction coupling was no longer sufficient to synchronise firing. When cells were stimulated by a continuous current injection there was an initial period of asynchronous burst firing followed after 120 msec by synchronous repetitive firing. This occurred as intracellular calcium fell due to reduced iCa(L) activity. The kinetics of one of the iCa(L) gate variables, which had a long activation time constant (τ range 18-150 msec), was responsible for this fall in iCa(L). The model makes predictions about the nature of the kinetics of the calcium current that will need experimental verification.